Repair of thermoplastic composites: an overview. (3rd April 2022) - Barroeta Robles, J.; Dubé, M.; Hubert, P.; Yousefpour, A.
Abstract: An extensive review of literature is conducted to present the evolution of the field of repair of thermoplastic composites (TPC's) from when it was first mentioned in 1980. The TPC materials used today in aerospace structures are introduced along with the existing challenges to repair TPC structures. The three most promising fusion bonding techniques to address these challenges (i.e. induction, resistance, and ultrasonic welding) are explained. The certification authorities have extensive knowledge and data for repair of thermoset polymer matrix composite structures. However, such level of knowledge is highly limited for TPC structures. A lack of robust processes and the overall lack of data on TPC's when compared to their thermoset counterparts are challenges that need to be addressed to implement TPC materials in aircraft structures. GRAPHICAL ABSTRACT: UF0001